Intraoperative optical coherence tomography imaging for assessment of anterior chamber gas fill - Tseng, Michael; Thau, Avrey; Berkowitz, Carla; Ramaprasad, Abhijit; Basti, Surendra (Frontiers in Ophthalmology, 2024)
IntroductionDuring endothelial keratoplasty, anterior chamber gas is titrated to a desired fill, which is difficult to optimize by visualization alone. This study evaluates how an anterior chamber gas fill correlates with intraocular pressure (IOP) and iris-angle configuration as identified by optical coherence tomography (OCT).MethodsEleven cadaveric eyes were studied in three configurations: baseline, air-fill just spanning limbus-to-limbus (“full-fill”), and air-fill maximally filling the anterior chamber (“overfill”). At each configuration, IOP was measured by Tonopen and iris-angle was determined by analyzing OCT images.ResultsNo differences in IOP or irisangles were identified between baseline and full-fill configurations (p=0.113 and p=0.152, respectively). When compared to overfill configuration, differences in IOP and iris-angles were identified for baseline (p<0.001 and p=0.001, respectively) and full-fill configuration (p=0.001 and p=0.039, respectively).DiscussionThese findings highlight that en-face visualization of full-fill may not be indicative of IOP elevation. A significant difference in IOP and iris-angle exists between full-fill and overfill configurations. Intraoperative OCT can serve as a useful surrogate to identify the extent of fill.